2011
DOI: 10.1007/s00226-011-0440-0
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic acceptance of wood in food industry

Abstract: Food is physically manipulated by other materials during production processes, and therefore, food quality and safety are vital in processes where foods are in contact with various materials. Wooden frames were used for centuries for dried egg pasta trays; however, with the development of different materials, wood was slowly abandoned and replaced by plastic. Nevertheless, there are some hygienic considerations concerning plastic frames in the dried egg pasta making industry. In this study, plastic and wooden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…However, it is unlikely that shelf life is influenced in dried powdered products with a very low moisture level and a water activity of <0.4. Hygiene levels in food processing facilities are typically monitored by swabbing of equipment and contact surfaces (Filip et al, 2012). Nevertheless, that method does not provide effective enumeration of airborne contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unlikely that shelf life is influenced in dried powdered products with a very low moisture level and a water activity of <0.4. Hygiene levels in food processing facilities are typically monitored by swabbing of equipment and contact surfaces (Filip et al, 2012). Nevertheless, that method does not provide effective enumeration of airborne contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…This step in pasta production is difficult and expensive and there are national regulations for reducing the water content. Filip and others () counted the total number of microorganisms on wood and plastic material used for pasta trays by a swabbing method. The authors analyzed 105 samples from wooden trays ( Abies spp .)…”
Section: Wood and Food Safety Assessmentmentioning
confidence: 99%
“…and 105 of plastic trays (PET) used for drying fresh pasta (Filip, Fink, Oder, & Jev snik, 2012). The authors showed that the total number of microorganisms (CFU/20 cm 2 ) was significantly lower on wooden frames compared to plastic frames and that 30% of swabs sampled from plastic frames exceeded 200 CFU/20 cm 2 , whereas the value for wooden frames was only 3%.…”
Section: Introductionmentioning
confidence: 96%